(untitled) (Research, Society and Development, 2021)
The incidence of foodborne diseases grows every year in Brazil, but it is estimated that a high number of cases is not reported. The objective of this work will be to carry out a retrospective study of the occurrence of outbreaks of foodborne diseases in the state of Maranhão, from 2007 to 2019, where a descriptive cross-sectional study was carried out, using as a database the Information on Notifiable Diseases - SINAN. During the study period, 48 outbreaks of foodborne diseases were identified in the state of Maranhão, with 2,535 patients. The etiologic agents identified were Salmonella sp. (6.25%), Escherichia coli (4.17%), rotavirus (4.17%), Staphylococcus aureus and coliforms, both with 2.08%, however, in 81.25% of outbreaks, the etiologic agent is not It was identified. The residence was the place of occurrence with the highest number of outbreaks (37.5%), followed by cases dispersed in the neighborhood (12.5%) and restaurant / bakery (10.42%), it is still important to mention the occurrence of 3 outbreaks (6.25%) in hospitals / health units. As for the origin, in 47.75% of the outbreaks, the food involved in the outbreak was not identified and water and mixed foods were the most common, with a frequency of 14.58% and 12.5%, respectively. As for the confirmation criteria, in 52.08% of the outbreaks the clinical-epidemiological criterion was used, 14.58% performed bromatological analyzes for confirmation and 10.42% only clinical, inconclusive and ignored criteria represented 22.92%. Differences in the number of outbreaks reported during the study period can result from a possible underreporting, causing gaps in the results found.